2021
DOI: 10.1111/1442-1984.12326
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seed dormancy and germination among populations of Silybum marianum (Asteraceae)

Abstract: Milk thistle (Silybum marianum) is a medicinal plant; however, lack of consistency in past dormancy studies has hindered propagation of this species from seeds. We tested the germination responses of freshly harvested and after‐ripened (stored for 2 and 7 months; 25°C at 50% relative humidity) seeds from three populations (P1, P2 and P3) in Iran at varying constant or alternating temperatures, with or without GA3 and in light and continuous darkness. No germination occurred in freshly harvested seeds incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In addition, the low water-use efficiency would hamper its spread into the surrounding sandy soils, as well as its ability to withstand increasingly frequent prolonged drought periods. The practically null emergence of plants during summer, even though some rainy episodes were recorded every studied year, would indicate that high temperatures (daily mean ≥ 24 °C) do not promote germination of this species [ 22 , 23 , 24 , 25 ], and/or that the seeds undergo some type of dormancy when they mature from which they are not released until late summer [ 10 , 26 , 27 , 28 , 29 ]. Similarly, once the mild temperatures of early autumn had passed (daily mean around 20 °C), the low temperatures (daily mean < 15 °C) of late autumn and winter considerably reduced germination, as occurs with many other species of the Asteraceae family [ 6 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the low water-use efficiency would hamper its spread into the surrounding sandy soils, as well as its ability to withstand increasingly frequent prolonged drought periods. The practically null emergence of plants during summer, even though some rainy episodes were recorded every studied year, would indicate that high temperatures (daily mean ≥ 24 °C) do not promote germination of this species [ 22 , 23 , 24 , 25 ], and/or that the seeds undergo some type of dormancy when they mature from which they are not released until late summer [ 10 , 26 , 27 , 28 , 29 ]. Similarly, once the mild temperatures of early autumn had passed (daily mean around 20 °C), the low temperatures (daily mean < 15 °C) of late autumn and winter considerably reduced germination, as occurs with many other species of the Asteraceae family [ 6 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance of the Temperature × Seed type interaction revealed that the central seeds were much more sensitive to temperature than the peripheral ones, germinating in 80% when the temperature was close to the optimum. However, up to 20% of central seeds still remained dormant, whose germination control could be internally regulated [ 10 , 27 ]. This leads us to think that most of the central seeds are released from dormancy at the end of summer and go into a quiescent state, being able to activate germination as soon as the environmental conditions are favorable for it.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations